THE EFFECT OF PROFITABILITY, LIQUIDITY, LEVERAGE, ACTIVITY, AND OPERATING CASH FLOW ON FINANCIAL DISTRESS IN CONSUMER SERVICES SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2022 - Syukri Hadi; Agustini Kimberly; Souvya Fitrie (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to determine the effect of Return on Asset (ROA), Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO) and Cash Flow to Sales on Financial Distress in Consumer Services Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2022 period. The object of this study is companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. The population in this study was 50 companies. The sampling technique used was the purposive sampling method and a sample of 22 companies was obtained. The data analysis technique used was multiple linear regression analysis using Smart PLS 4.0 because the research data was not normally distributed. The results of this study indicate that the Current Ratio (CR) variable affects Financial Distress. Meanwhile, the variables Return on Asset (ROA), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO) and Cash Flow to Sales do not affect Financial Distress in the consumer services sub-sector listed on the Indonesia Stock Exchange for the 2018-2022 period. Penelitian ini bertujuan untuk mengetahui pengaruh Return on Asset (ROA), Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turn Over (TATO) dan Cash Flow to Sales Terhadap Financial Distress Pada Perusahaan Jasa Sub-Ektor Jasa Konsumen Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022. Objek penelitian ini adalah perusahaan yang terdaftar di Bursa Efek Indonesia periode tahun 2018 sampai dengan 2022. Populasi dalam penelitian ini adalah 50 perusahaan. Teknik pengambilan sampel yang digunakan adalah metode purposive sampling dan diperoleh sampel sebanyak 22 perusahaan. Teknik analisis data yang digunakan adalah analisis regresi linear berganda dengan menggunakan Smart PLS 4.0 yang dikarenakan data penelitian tidak berdistribusi normal. Hasil dari penelitian ini menunjukkan bahwa variabel Current Ratio (CR) berpengaruh terhadap Financial Distress. Sedangkan variabel Return on Asset (ROA), Debt to Asset Ratio (DAR), Total Asset Turn Over (TATO) dan Cash Flow to Sales tidak berpengaruh terhadap Financial Distress pada Sub-sektor Jasa Konsumen Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022.